Você está na página 1de 2

352 Solutions Manual

Solutions to Chapter 28 Problems


S.28.1

The solution is obtained directly from Eq. (28.9) in which ∂c1 /∂α = a, α = α0 and
cm,0 = CM,0 . Thus
 
CM,0 cos λ(s − y)
θ= + α0 −1
ea cos λs
which gives
 
CM,0 cos λ(s − y) CM,0
θ= + α0 − − α0
ea cos λs ea
Thus
 
CM,0 cos λ(s − y) CM,0
θ + α0 = + α0 −
ea cos λs ea
where
ea 21 ρV 2 c2
λ2 =
GJ
Also, from Eq. (28.11) the divergence speed Vd is given by

π2 GJ
Vd =
2ρec2 s2 a

S.28.2

Since the additional lift due to operation of the aileron is at a distance hc aft of the
flexural axis the moment equilibrium equation (28.25) for an elemental strip becomes
dT
δy − Lec − Lξ hc = 0 (i)
dy
in which, from Eq. (28.23)
1 2  py  
L = ρV cδy a1 θ − + a2 fa (y)ξ
2 V
where fa (y) = 0 for 0 ≤ y ≤ ks and fa (y) = 1 for ks ≤ y ≤ s. Also
Lξ = 21 ρV 2 cδya2 fa (y)ξ

Then, substituting for T (= GJ dθ/dy), L and Lξ in Eq. (i) and writing λ2 =


ρV 2 ec2 a1 /2GJ
d2 θ py h a2
2
+ λ2 θ = λ2 + λ2 fa (y)ξ (ii)
dy V e a1
Solutions to Chapter 28 Problems 353

The solution of Eq. (ii) is obtained by comparison with Eq. (28.29). Thus
 
p sin λy ha2 ξ
θ1 (0 − ks) = y− − ( tan λs cos λks − sin λks) sin λy (iii)
V λ cos λs ea1
and
 
p sin λy
θ2 (ks − s) = y−
V λ cos λs
ha2 ξ
+ (1 − cos λy cos λks − tan λs cos λks sin λy) (iv)
ea1
Then, from Eq. (28.32)
  
ks py  s py  s
a1 θ1 − y dy + a1 θ2 − y dy = −a2 ξ y dy (v)
0 V ks V ks

Substituting for θ1 and θ2 in Eq. (v) from Eqs (iii) and (iv) gives
   
s ks s (e + h) s
− tan λs y sin λy dy + tan λks y sin λy dy − y cos λy dy + y dy
0 0 ks h cos λks ks
 s
pea1
= y sin λy dy
ha2 ξλV cos λs cos λks 0

Hence the aileron effectiveness is given by


 s  ks
− tan λs y sin λy dy + tan λks y sin λy dy
0 0
 s
(e + h) 2
− y cos λy dy + [s − (ks)2 ]
(ps/V ) 2h cos λks
= ks  s (vi)
ξ ea
y sin λy dy
ha2 λs cos λs cos λks 0

The aileron effectiveness is zero, i.e. aileron reversal takes place, when the numerator
on the right-hand side of Eq. (vi) is zero, i.e. when
 ks  s  s
(e + h)
tan λks y sin λy dy − tan λs y sin λy dy − y cos λy dy = [(ks)2 − s2 ]
0 0 ks 2h cos λks